Perinatal Outcomes in Multiple Pregnancies: Challenges and Management Strategies (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Twin pregnancies is generally accepted as a high-risk condition with greater maternal and neonatal morbidity compared to singleton gestations.Objective: This study was designed to evaluate Obstetrics and Gynaecology difficulties and management strategies of different hospitals in Iraq, by recruiting and studying perinatal outcomes for twin pregnancies versus singleton pregnancies.Methods: A cross-sectional study was conducted among 70 patients who delivered from January 2024 to January 2025. The cohort was divided into twin pregnancies (n=37) and age-matched singleton pregnancies (n=33). Maternal characteristics, delivery data, and neonatal outcomes were recruited and assessed through medical records.Results: The mean age of women with twin pregnancies was higher (32.1 vs. 29.3 years), and Assisted Reproductive Technology was more prevalent (29.7% vs. 6.1%). Preeclampsia (18.9% vs. 3.0%) and preterm birth